2012
DOI: 10.1111/j.1654-1103.2012.01440.x
|View full text |Cite
|
Sign up to set email alerts
|

Do we need soil moisture measurements in the vegetation–environment studies in wetlands?

Abstract: Questions Water level parameters are normally used as explanatory variables in ecological studies, but soil moisture may be more causally connected with species composition. Can measurements of volumetric soil moisture in vertical profiles using electromagnetic sensors improve vegetation–environment analyses in fens and bogs? Are there inter‐habitat differences in water level–moisture relationships that could explain different sensitivities of particular vegetation types to water level changes? Location Calcar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…Soil moisture has historically been difficult to measure cheaply, accurately and quickly under field conditions (Hájek et al ., ). Moreover, as topography and derived indices can be strongly correlated with soil moisture, proxy variables have often been used as surrogates instead (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Soil moisture has historically been difficult to measure cheaply, accurately and quickly under field conditions (Hájek et al ., ). Moreover, as topography and derived indices can be strongly correlated with soil moisture, proxy variables have often been used as surrogates instead (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…Parviainen et al ., ; Piedallu et al ., ). However, with the development of new technologies, a shift to explicit measures of soil wetness is possible (Hájek et al ., ). Our results suggest that studies examining fine‐scale vegetation patterns should be based on field‐quantified soil moisture measurements where possible, because TWI was weakly related to observed soil moisture (as observed by, e.g.…”
Section: Discussionmentioning
confidence: 97%
“…However, the predictive power of TWI differed among habitat types. In a study of the contribution of water table level versus soil moisture in explaining species composition, Hájek et al (2013) found that deep peat layers buffer the effect of water level decline, an effect which was detected by direct measurements of soil moisture, but not water table depth. This may be why we see weak predictive power of TWI on mean Ellenberg F values in habitats like active raised bogs, transition mires and quaking bogs, and depression on peat substrates (habitat code 7110, 7140, and 7150).…”
Section: Discussionmentioning
confidence: 99%
“…This may be why we see weak predictive power of TWI on mean Ellenberg F values in habitats like active raised bogs, transition mires and quaking bogs, and depression on peat substrates (habitat code 7110, 7140, and 7150). Hájek et al (2013) conclude that soil organic matter must be included to account for water retention abilities of different soil types. Furthermore, in groundwater-dependent habitats such as fens and bogs, community-weighted Ellenberg F was not controlled by topographically determined water availability.…”
Section: Discussionmentioning
confidence: 99%
“…The role of soil moisture is often underestimated in studies regarding high-latitude and high-alpine landscapes, due to the lack of data (Kammer et al, 2013;le Roux et al, 2013;Myers-Smith et al, 2015). Spatially extensive soil moisture measurements are challenging, since they are time-consuming, expensive, and hard to obtain (Famiglietti et al, 2008;Hajek et al, 2013). Thus, terrain-based surrogates, such as wetness indices, are commonly used in the absence of field-obtained soil moisture data.…”
Section: Introductionmentioning
confidence: 99%